The Over-40-Years-Epidemic of Infectious Bursal Disease Virus in China - Zhang, Wenying; Wang, Xiaomei; Gao, Yulong; Qi, Xiaole (Viruses, 2022)
Infectious bursal disease (IBD) is an acute, highly contagious, immunosuppressive disease of chickens caused by the virus (IBDV), which critically threatens the development of the global chicken industry and causes huge economic losses. As a large country in the poultry industry, the epidemic history of IBDV in China for more than 40 years has been briefly discussed and summarized for the first time in this report. The first classic strain of IBDV appeared in China in the late 1970s. In the late 1980s and early 1990s, the very virulent IBDV (vvIBDV) rapidly swept across the entirety of China, threatening the healthy development of the poultry industry for more than 30 years. Variants of IBDV, after long-term latent circulation with the accumulation of mutations since the early 1990s, suddenly reappeared as novel variant strains (nVarIBDV) in China in the mid-2010s. Currently, there is a coexistence of various IBDV genotypes; the newly emerging nVarIBDV of A2dB1 and persistently circulating vvIBDV of A3B3 are the two predominant epidemic strains endangering the poultry industry. Continuous epidemiological testing and the development of new prevention and control agents are important and require more attention. This report is of great significance to scientific cognition and the comprehensive prevention and control of the IBDV epidemic.